INVESTIGATING EFL STUDENTS’ SATISFACTION AND EXPECTATION IN VIRTUAL LEARNING ENVIRONMENTS - Yasa, I Gede Bayu Kartika; Santosa, Made Hery; Kusuma, I Putu Indra (Premise: Journal of English Education and Applied Linguistics, 2023)
Online learning became a learning adaptation during the COVID-19 pandemic, and in the post-pandemic era, learning still implements online learning in blended learning. The satisfaction and expectation terms were used to measure the effectiveness of online learning during the COVID-19 pandemic and prepare for a practical blended learning experience. This study aims to investigate EFL junior high school students’ satisfaction with online learning and delve into the students’ expectations of blended learning in the post-pandemic era. An explanatory sequential mixed method design was conducted through an online survey of 151 eighth-grade students and interviews with ten students among the survey respondents comprising five in each high and low satisfaction category. The study collected the data through a purposive sampling technique analyzed using descriptive analysis for the quantitative data and thematic analysis for the qualitative data. The result explained that most students were satisfied with online learning: instructor pedagogical skills, interaction, technology, and learning resources factor. Furthermore, for blended learning, the students expect to keep blended learning and be able to use technology used in online learning, such as a smartphone. These results help the EFL teacher to raise students’ satisfaction with online and blended learning at the junior high school level.